(untitled) (Journal of Parents and Teachers, 1996)
The article addresses environmental issues and the importance of acting in the theatrical context, highlighting the relevance of the actors’ interpretation and lighting in the performance. The influence of history and culture on theater is mentioned, as well as the connection between everyday life and art. In addition, reference is made to the evolution of theater since the Middle Ages and its relationship with cultural and social elements.